The use of ofatumumab in the treatment of B-cell malignancies. (December 2017) - Soe, Zar Ni; Allsup, David
Ofatumumab has been extensively studied in the treatment of B-cell malignancies. Currently, it has been approved for the treatment of chronic lymphocytic leukemia in a number of different situations. However, there is still no compelling evidence confirming the superiority of ofatumumab over rituximab in vivo . In this article, we summarize the currently available clinical data supporting the use of ofatumumab in the treatment of B-cell malignancies. The clinical studies were searched fromclinicaltrials.gov with the key words ofatumumab, HuMax-CD20. Out of 115 trials available, studies for B-cell malignancies were selected, followed by selection of completed studies with results and active ongoing studies. The results from completed studies were thoroughly analyzed and active ongoing studies were listed in tables.